2020
DOI: 10.3390/pathogens9050330
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis Provides Insights into the Phylogeny, Resistome, Virulome, and Host Adaptation in the Genus Ewingella

Abstract: Ewingella americana is a cosmopolitan bacterial pathogen that has been isolated from many hosts. Here, we sequenced a high-quality genome of E. americana B6-1 isolated from Flammulina filiformis, an important cultivated mushroom, performed a comparative genomic analysis with four other E. americana strains from various origins, and tested the susceptibility of B6-1 to antibiotics. The genome size, predicted genes, and GC (guanine-cytosine) content of B6-1 was 4.67 Mb, 4301, and 53.80%, respectively. The origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 115 publications
(127 reference statements)
0
13
0
Order By: Relevance
“…Our case is notable not only for the unique organism but for its incredibly multidrug-resistant nature (Table 4). Also, based on the recommendations of the Clinical and Laboratory Standards Institute, they concluded that E. americana is resistant to many antibiotics (Table 5) [9]. It was found that E. americana contains about 67 putative virulence genes [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our case is notable not only for the unique organism but for its incredibly multidrug-resistant nature (Table 4). Also, based on the recommendations of the Clinical and Laboratory Standards Institute, they concluded that E. americana is resistant to many antibiotics (Table 5) [9]. It was found that E. americana contains about 67 putative virulence genes [9].…”
Section: Discussionmentioning
confidence: 99%
“…Also, based on the recommendations of the Clinical and Laboratory Standards Institute, they concluded that E. americana is resistant to many antibiotics (Table 5) [9]. It was found that E. americana contains about 67 putative virulence genes [9]. The virulence features include the secretion system, adherence, invasion, chemotaxis, motility, immune evasion, and pore-forming toxins [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1a and S1) originating from essentially any environments like soil, plants, higher eukaryotes including mammals, or the marine environment. [4,5,[13][14][15] In general, ape BGCs consist of genes encoding unusual type II polyketide synthases (PKSs), enzymes involved in lipid biosynthesis, and membrane proteins for localization ( Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%